Integration of The Accountant's Code of Ethics Perspective of Betawi Cultural Values - Muhammad Aras Prabowo; Muhamad Hasan Syadzily; Sintia Nur Afifah (Innovation Business Management and Accounting Journal, 2025)
This research aims to integrate Betawi cultural values ​​with accountant ethics. This research uses a literature review method with descriptive data analysis. Data sources are journals, books and references related to the code of ethics for accountants and Betawi culture. The research results show integration between the accountant's code of ethics and Betawi cultural values. These values ​​include; (1) honest (our people, don't lie too much), (2) tough (firm in his stance and not easily influenced by people), (3) enthusiastic (able to work seriously), (4) agile (careful and neat), (5) kitchen secret (able to keep secrets). These five values ​​are a code of ethics for accountants based on Betawi culture. It is hoped that further research will deepen Betawi cultural values ​​by integrating the accountant's code of ethics, for example using phenomenological or ethnographic methods.